Towards A Better Understanding of Hypervigilance in Combat Veterans. (3rd April 2019) - Cameron, Amy Y.; Mamon, Daria
Abstract: Hypervigilance is common among combat veterans because of long-term exposure to elevated stress levels and specific military training that encourages and rewards heightened attention and arousal to potential threat. Although empirically supported treatments for PTSD are efficacious, many individuals remain symptomatic after completion of treatment, and many combat veterans report hypervigilance as an ongoing, problematic symptom in clinical settings. This article provides relevant research and hypotheses about persistent hypervigilance in combat veterans from both cognitive-behavioral and neuropsychological literature. Treatment implications and future research suggestions are presented.